2021
DOI: 10.1134/s1063785021060110
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Flow Structure in the Vicinity of the Pulsed Surface Arc Discharge in a Magnetic Field

Abstract: The structure of a flow that appears during the motion of a pulsed surface arc discharge in a transverse magnetic field is described. It is shown that the motion of the plasma channel leads to the formation of a toroidal vortex. The typical velocity of gas inflow to the wall in the aerodynamic wake of the arc was 30-50 m/s and corresponded to the value of up to 40% of the maximum expansion velocity of the gas during the current pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The vertical velocity in the vortex, required to create an observed disturbance, is in the order of 10-20 m/s. It qualitatively corresponds to the typical velocity obtained during the collapse of the hot cavern in the late stages of the current pulse [27]. The vortex intensity does not depend on the local flow velocity, since the momentum coefficient is rather high, C µ > 1, and the pulse duration is in the order of the convection time, τ = D/U 0 ∼ 90 µs, at U 0 = 80 m/s.…”
Section: Boundary Layer Thickness and Free-stream Velocity Effectsupporting
confidence: 76%
See 2 more Smart Citations
“…The vertical velocity in the vortex, required to create an observed disturbance, is in the order of 10-20 m/s. It qualitatively corresponds to the typical velocity obtained during the collapse of the hot cavern in the late stages of the current pulse [27]. The vortex intensity does not depend on the local flow velocity, since the momentum coefficient is rather high, C µ > 1, and the pulse duration is in the order of the convection time, τ = D/U 0 ∼ 90 µs, at U 0 = 80 m/s.…”
Section: Boundary Layer Thickness and Free-stream Velocity Effectsupporting
confidence: 76%
“…The efficiency of flow acceleration can be as high as 2-3%, exceeding the efficiency of DBD or corona discharge by more than an order of magnitude. The flow structure around a magnetically driven arc was studied in [24,25], and recently, in more detail in [26,27]. It was shown that inside the conductive channel and in its close vicinity, two counter-rotating vortices are formed, driven by the inhomogeneity of the magnetic force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation